Long-term high intake of 9-PAHPA or 9-OAHPA increases basal metabolism and insulin sensitivity but disrupts liver homeostasis in healthy mice - Benlebna, Melha; Balas, Laurence; Bonafos, Béatrice; Pessemesse, Laurence; Vigor, Claire; Grober, Jacques; Bernex, Florence; Fouret, Gilles; Paluchova, Veronika; Gaillet, Sylvie; Landrier, Jean François; Kuda, Ondrej; et al. (Journal of nutritional biochemistry, 2020)
Branched fatty acid esters of hydroxy fatty acids (FAHFAs) are a new family of endogenous lipids recently discovered. Several studies reported that some FAHFAs have antidiabetic and anti-inflammatory effects. The objective of this study was to explore the impact of two FAHFAs, 9-PAHPA or 9-OAHPA, on the metabolism of mice. C57Bl/6J male mice, 6 weeks old, were divided into 3 groups of 10 mice each. One group received a control diet and the two others groups received the control diet supplemented with 9-PAHPA or 9-OAHPA for 12 weeks. Mouse weight and body composition were monitored throughout the study. Some days before euthanasia, energy expenditure, glucose tolerance and insulin sensitivity were also determined. After sacrifice, blood and organs were collected for relevant molecular, biochemical and histological analyses. Although high intake of 9-PAHPA or 9-OAHPA increased basal metabolism, it had no direct effect on body weight. Interestingly, the 9-PAHPA or 9-OAHPA intake increased insulin sensitivity but without modifying glucose tolerance. Nevertheless, 9-PAHPA intake induced a loss of glucose-stimulated insulin secretion. Surprisingly, both studied FAHFAs induced hepatic steatosis and fibrosis in some mice, which were more marked with 9-PAHPA. Finally, a slight remodeling of white adipose tissue was also observed with 9-PAHPA intake. In conclusion, the long-term high intake of 9-PAHPA or 9-OAHPA increased basal metabolism and insulin sensitivity in healthy mice. However, this effect, highly likely beneficial in a diabetic state, was accompanied by manifest liver damage in certain mice that should deserve special attention in both healthy and pathological studies.
Keywords: Liver; Animals; homeostáza; mastné kyseliny; glukózový toleranční test; zánět; játra; Adipose Tissue, White; Fatty Liver; Liver Cirrhosis; bazální metabolismus; Fatty Acids; Basal Metabolism; jaterní cirhóza; energetický metabolismus; Blood Glucose; Glucose Tolerance Test; Lipid Metabolism; Mice; Homeostasis; ztučnělá játra; Energy Metabolism; Insulin; myši; metabolismus lipidů; Inflammation; tělesná hmotnost; Male; Insulin Resistance; inzulinová rezistence; Body Weight; zvířata; mužské pohlaví; Mice, Inbred C57BL; bílá tuková tkáň; inzulin; krevní glukóza; myši inbrední C57BL